Impact of Agricultural Policies on Agripreneurship Development in Nasarawa State - ORISAREMI, Joseph Omeiza; AHMADU, Noel Donald; ORISAREMI, Christiana Upe (Covenant Journal of Entrepreneurship, 2023)
This study examined the influence of agricultural policy on agripreneurship development in Nasarawa state. The study adopted survey design. The population of the study consists of 2076 agripreneurship managers operating their businesses within Nasarawa State area. The study objectives are to ascertain how specific agricultural policies and programmes have affected food security, poverty reduction and employment generation. Taro Yamane’s sampling technique was used to derived the sample size of 335. Simple linear regression analysis was used to test the hypotheses formulated for the study. The findings revealed that agricultural policy has a significant effect on employment generation, (f- test 96.749 and p-value p of 0 .000), agricultural policy also has a significant effect on poverty alleviation (f-test 200,756 and p-value of 0.000) and moreover, agricultural policy has a significant effect on food security (f-test 86.568 and p-value of 0,000) in Nasarawa state. The study concludes that agripreneurship policy has a positive and significant effect on agripreneurship development in Nasarawa State. The study therefore, recommends that farmers should be encouraged to establish safe storage facilities as it is very important for food security, as it as well help to stabilize food price. There is also need to increase agricultural production, preservation of unused produce or unsold items are equally as important to cutting waste.